ORGANIZATIONAL-PEDAGOGICAL CONDITIONS OF FORMING PROFESSIONAL COMPETENCE IN FUTURE PEDAGOGUES - Konovalova, Ludmila; Skvortsov, Vyacheslav (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In the article is considering possibilities of realization of competence-based approach in process of training future pedagogues in a higher education institution. The author proves main ideas of educational strategy that provide with effectiveness of forming professional competence in pedagogues. The content of the article shows the importance of integration educational, scientific and pedagogic activity in the process of development of professional competence in future pedagogues. It describes principles, modes and methods of effective organization of professional competence in future pedagogues during process of education in a higher education institution.